Effect of sevelamer on serum phosphorus levels in chronic kidney disease and hemodialysis patients; a systematic review and meta-analysis - Farshad Gharebakhshi; Mohammad Hossein Taklif; Arash Izadpanah Ghahremani; Mohamad Khaledi; Sara Abbasian; Seyedeh Mahsa Shariati Sough; Fatemeh Vashahi Torfi; Hamidreza Khodabandeh; Elnaz Hajian (Journal of Nephropathology, 2024)
Introduction: Hyperphosphatemia is an independent risk factor for mortality in chronic kidney disease (CKD) patients. Objectives: This systematic review and meta-analysis aimed to investigate the effect of Sevelamer on serum phosphorus levels in CKD and hemodialysis patients. Materials and Methods: The data were obtained after searching the international databases of Cochrane, PubMed, Scopus, Web of Science, and the Google Scholar search engine until February 28, 2023. The heterogeneity of articles was assessed using the I2 index. The data were analyzed in STATA 14, and P values < 0.05 were considered significant. Findings: A total of 22 articles were assessed with a total sample size of 3221. Sevelamer reduced calcium levels in CKD and hemodialysis patients compared with those in the comparison group (standardized mean difference [SMD]: -0.67; 95% CI: -1.23, -0.11); however, sevelamer had no significant effect on serum parathyroid hormone (PTH) levels (SMD: 0.07; 95% CI: -0.39, 0.54) and Ca × P product (SMD: -0.20; 95% CI: -0.41, 0). A significant decrease in serum phosphorus level was observed in patients who had taken sevelamer for a maximum of 12 weeks compared with the comparison group (SMD: -0.27; 95% CI: -0.54, -0.01); however, no significant decrease in serum phosphorus level was observed in patients who had taken sevelamer for more than 12 weeks. A significant decrease in serum phosphorus level was observed in sevelamer users compared to placebo group members (SMD: -0.36; 95% CI: -0.68, -0.05). Conclusion: The administration of sevelamer reduced serum phosphorus levels in CKD and hemodialysis patients compared with those in the placebo group in the short term. Therefore, physicians are recommended to prescribe sevelamer for a maximum period of three months. Registration: This study has been compiled based on the PRISMA checklist, and its protocol was registered on the PROSPERO website (ID: CRD42023406804).